MODERN CLINICAL SCIENCE BEGAN WITH SANTORIO SANTORIO (1561-1636) - Natale G. De Santo; Carmela Bisaccia; Antonio Mezzogiorno; Alessandra Perna; Massimo Cirillo (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2015)
Santorio Santorio (1561-1636), born in Capodistria, a  Venice Republic territory, (now Koper in Slovenia), student, medical doctor, and professor of theoretical medicine  at the university of Padua, marked the beginning of  modern medicine. Santorio introduced measurements and mathematics into human experimentation. By means of a weighing machine, over a 30-year period, he investigated on more than ten thousand persons, including Galileo Galilei. He used to measure daily body weight, along with the quantity of ingested food and drink, and the quantity of body discharges (urine and feces) so that he could calculate the insensible perspiration which he used  as a dual token to characterize health and disease, to cure patients after knowing their physical parameters including the pulse and the temperature. His main work was De statica medicina, a well received book which had more than 40 editions during the 17th and 18th century and was translated into English, Italian, French and German. A book small but praised by Boerhaave, von Haller and Lavoisier which granted to Santorio the definition of Galilean, by many historians of medicine including Salvatore De Renzi, Castiglioni, Pucinotti and Pazzini. Santorio embodied the modern physician-scientist, continually experimenting on humans and immediately transforming into medical devices using the data originating in basic science. So the findings repported in the books were immediately used to help patients. He also introduced self-experimentation in medicine, an important problem even nowadays. Although he was aware that the university took credit for his work, he respected the institution from which he obtained a salary for life even when he stopped the teaching at the University. So he even showed his modernity: pioneer in granting to the University of Padua, through his last will, money for yearly scholarships.